Experiential Learning Model to Enhance Environmental Literacy Competence in High School Students - Rio Christy Handziko; Muhammad Cahya Nugraha (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
The objectives of this research are to evaluate the potential of an Adiwiyata (Eco-school) public high school environment in Yogyakarta as a learning resource for biodiversity topics; to observe the ratio of teacher and student activities in the teaching and learning process using the experiential learning model; to examine the influence of the experiential learning model in facilitating students' learning styles; and to determine the improvement of students' environmental literacy competencies in the domains of knowledge, cognition, and communication within the biodiversity curriculum. This study was conducted with 10th-grade students using a purposive sampling technique involving both experimental and control classes. Data were collected through observations of learning resource potential, documentation, pretest-posttest, interviews, learning implementation records, teacher-student activity ratios, group communication assessments, and the distribution of environmental attitude questionnaires. Data were analyzed using an independent sample t-test via SPSS 30.0 for Windows. The results indicate that the high school environment possesses significant potential as a learning resource, the experiential learning model enhances student engagement, all student learning styles are effectively accommodated, and learning through direct interaction with biological study objects is proven effective in improving students' environmental literacy skills.